1997
DOI: 10.1073/pnas.94.23.12688
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of neurons, synapses, and neuropil and glial activation in a murine Atm knockout model of ataxia–telangiectasia

Abstract: Neural degeneration is one of the clinical manifestations of ataxia-telangiectasia, a disorder caused by mutations in the Atm protein kinase gene. However, neural degeneration was not detected with general purpose light microscopic methods in previous studies using several different lines of mice with disrupted Atm genes. Here, we show electron microscopic evidence of degeneration of several different types of neurons in the cerebellar cortex of 2-month-old Atm knockout mice, which is accompanied by glial acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
62
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 17 publications
5
62
0
Order By: Relevance
“…41,44,45 Electron microscopy observations have detected structural activation of glial cells in Atm knockout mice. 46 Ultrastructural alterations in astrocytes have been demonstrated alongside neuronal degenerative processes in Atm Ϫ/Ϫ mice in cerebellar tissue. 46 Furthermore, astrocytes from Atm Ϫ/Ϫ mice exhibited growth arrest and growth defects, which may be due to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41,44,45 Electron microscopy observations have detected structural activation of glial cells in Atm knockout mice. 46 Ultrastructural alterations in astrocytes have been demonstrated alongside neuronal degenerative processes in Atm Ϫ/Ϫ mice in cerebellar tissue. 46 Furthermore, astrocytes from Atm Ϫ/Ϫ mice exhibited growth arrest and growth defects, which may be due to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…46 Ultrastructural alterations in astrocytes have been demonstrated alongside neuronal degenerative processes in Atm Ϫ/Ϫ mice in cerebellar tissue. 46 Furthermore, astrocytes from Atm Ϫ/Ϫ mice exhibited growth arrest and growth defects, which may be due to oxidative stress. 41,47 Retinal neurons are terminally differentiated and are therefore, like other neurons in the brain, irreplaceable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ATM deficiency in the Atm À/À mouse brain results postnatally in deficient dendritogenesis in Purkinje neurons 9 as well as reduced cell size and diminished cell density in substantia nigral dopaminergic neurons. 8,10 Atm À/À mice also show 'predegenerative' CNS lesions with age-dependent neuronal cell loss and gliosis, 11 dystrophic Purkinje cells, 12 and indicators of Purkinje cell cycle re-entry postnatally. 13 It has also been reported that in vitro survival of cerebellar Purkinje cells from Atm À/À mice is significantly reduced compared with their wild-type littermates.…”
mentioning
confidence: 99%
“…However, the tested cells were not the most relevant cell targets for A-T treatment, as cerebellar neural cells are thought to be the primary targets for abrogating neurodegeneration in patients. Furthermore, Atm knockout (Atm À / À ) mice do not manifest the progressive ataxia seen in A-T patients and also fail to show marked loss of Purkinje cells (PCs) in the cerebellum, currently believed to be a hallmark of the ATM-related neural deficits observed in disease [16][17][18] .…”
mentioning
confidence: 99%